New Route to Direct Synthesis of Symmetrical Ureas from Carboxylic Acids - Jahani, Daniel; Yassine, Hasna; Khouili, Mostafa; Pujol, M. Dolors (Synthesis, 2023)
The first method for the direct conversion of carboxylic acids into ureas has been developed. The classical procedures described for the formation of ureas from carboxylic acids require two steps, preparation of the isocyanate followed by its aminolysis. In this work, aryl carboxylic and arylalkyl carboxylic acids have been transformed into symmetric ureas in a single step using DPPA or sodium azide as nitrogen source. The addition of water (method A) or the presence of solvent water (method B) was essential for the formation of symmetrical ureas from the corresponding carboxylic acids. The corresponding ureas have been obtained in good to excellent yields of 46 to 100%. This procedure is compatible with different substituents present in the starting carboxylic acid.
Keywords: urea; carboxylic acid; isocyanate; DPPA; sodium azide